2021
DOI: 10.3390/jcm10194614
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Infectious Complications after Esophagectomy for Esophageal Cancer on Cancer Prognosis and Treatment Strategy

Abstract: Despite advances in the perioperative management of esophagectomy, it is still a highly invasive procedure for esophageal cancer and is associated with severe postoperative complications. The two major postoperative infectious complications after esophagectomy are pulmonary complications and anastomotic leakage. We previously reported that postoperative infectious complications after esophagectomy adversely affect long-term survival significantly in a single institution and meta-analysis. Additionally, we revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…We previously reported that the intensive postoperative inflammatory response after esophagectomy was significantly correlated with poor OS [ 23 , 24 ]. Surprisingly, in this study, high PCT levels in the early postoperative period were significantly correlated with good OS, suggesting that elevated PCT in the early postoperative period is not an inflammatory response, but a positive response for survival.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the intensive postoperative inflammatory response after esophagectomy was significantly correlated with poor OS [ 23 , 24 ]. Surprisingly, in this study, high PCT levels in the early postoperative period were significantly correlated with good OS, suggesting that elevated PCT in the early postoperative period is not an inflammatory response, but a positive response for survival.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies [14][15][16][17] have shown that complications after esophageal cancer surgery can lead to poor prognosis in patients with esophageal cancer. In addition, both the study by Ayako [18] et al and the study by Eisuke [8] et al found that postoperative pneumonia after esophageal cancer was an independent risk factor for poor prognosis. In addition, in the study of Li [19] et al, 26 patients with both esophageal and gastric cancer had no significant difference in median OS compared with patients with esophageal cancer alone.…”
Section: Discussionmentioning
confidence: 96%
“…However, postoperative complications of esophageal cancer still occur, and complications such as anastomotic leakage significantly increase patient mortality [7]. In addition, previous studies [8] have shown that there is a significant correlation between complications and the long-term survival of patients with esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has been shown that early detection of PIC is essential not only for the treatment of complications but also for patient survival [ 20 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. PICs, according to the definition used for this paper, include surgical site infections, pneumonia, pleural empyema, leakage or necrosis of the gastric conduit, and anastomotic leakage [ 33 , 39 ]. Indisputably, these complications are of different importance and severity.…”
Section: Discussionmentioning
confidence: 99%